THE IMPLEMENTATION OF FAMILY PLANNING VILLAGE PROGRAM IN DADAPSARI VILLAGE, NORTH SEMARANG SUBDISTRICT BASED ON THE CENTRAL JAVA GOVERNOR REGULATION NUMBER 77 YEAR 2017 - Tampubolon, Heberina Trinatis; Purnaweni, Hartuti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Indonesia is ranked 4th in the world as the largest population after China, India and the United States with a population growth rate of 3 million to 4 million people per year. One of the cities that have high population growth is Semarang with the population growth rate of 1.65% in which it is also claimed as the highest rate of population growth in Central Java province. Besides, Semarang has a number of productive ages reaching 74%. To manage the rate of population growth in order to get closer to the family planning program, it is established a family planning program called KB village in RW IV Dadapsari. Dadapsari village has a population growth rate of 1% with 66% population of productive age. The purpose of this study is to determine the implementation of the Dadapsari KB village program based on the Central Java Governor Regulation Numb. 77 of 2017 which is about the establishment and coaching. This research is a descriptive qualitative research. The result of the study shows that Dadapsari KB Village has been established in accordance with several criteria called main criteria, regional criteria and specific criteria. The main criteria include families with low rate of family planning participation which are 52% population of early age marriages. The regional criteria include families who live in slums, densely populated, near the railroad and river banks. The specific criteria involve the population with low income and low level of education. Population activities such as BKB, BKL, BKR and cadre coaching have not been carried out optimally. Activities planning should involve the community and refers to community needs. Evaluation activities are not routinely carried out and lastly conducted in 2017. Moreover, community participation in the program is still lack. Some suggestions that can be done are giving rewards for the cadres, creating activity innovation in the Dadapsari Family Planning village and providing more socialization from the Population and Family Planning Control Agency (DPPKB) to the community.